Do Digitalization and Startups Contribute to the Development of the Agroindustry Sector? - Syahruddin Yasen (Department of Business and Entrepreneurship, Faculty of Economics and Business, Universitas Negeri Makassar, 2024)
This research aims to analyze the preferences and other factors influencing consumer decisions related to Markisa Mammiri products. The respondents selected are undergraduate students from the Faculty of Economics and Business, Universitas Negeri Makassar, with data collection conducted online through Google Forms with 37 respondents. The descriptive analysis results indicate that most respondents gave positive ratings for digital accessibility, digital promotion, customer satisfaction, product price, and social economic impact. However, there is relatively lower rating for product quality. It is recommended to develop a strategy focusing on improving product quality through strengthening the R&D department, implementing strict quality control, enhancing communication and education with customers, as well as innovative product and customer service development. It is hoped that the continuous application of this strategy will increase customer satisfaction and strengthen the company's position in the market. This research provides valuable insights for business development strategies to achieve higher customer satisfaction and sustainable growth for Markisa Mammiri's business.